MRI of the Prostate in Germany: Online Survey among Radiologists - Mueller-Lisse, U. G.; Lewerich, B.; Mueller-Lisse, U. L; Reiser, M.; Scherr, M. K. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Purpose: To assess structural, technical, and communicative aspects of dedicated MR examinations of the prostate (MRP) offered by radiologists in Germany.Materials and Methods: We conducted an eight-item online survey among members of the German Radiology Society (DRG). Radiological institutions were asked about their structure, i. e., either hospital department (HD) or private practice (PP), number of board-certified radiologists, postal regions, number of MRPs in 2011, MR technology and MR sequences applied, ways to communicate results, and feedback from referring physicians on results of subsequent tests and procedures. Submissions were cleared of redundancies and anonymized. Differences in the number of positive replies to each item were statistically significant at p < 0.05 for two-tailed testing in 2x2 tables.Results: The survey represented board-certified radiologists in 128 institutions (63 HDs and 65 PPs) in 67/95 German postal regions (71 %). Almost two-thirds of institutions performed 11 to 50 MRPs in 2011, more often at 1.5 T (116/128, 91 %) than at 3.0 T (36/128, 28 %), and most frequently with surface coils (1.5 T, 88/116, 76 %; 3.0 T, 34/36, 94 %; chi-square, 1.9736, 0.1 < p < 0.25). About two-thirds of 1.5 T users and 90 % of 3.0 T users applied at least one functional MR modality (diffusion-weighted imaging, dynamic contrast-enhanced imaging, or MR spectroscopy) for MRP. Reports including graphic representations of the prostate were applied by 21/128 institutions (16 %). Clinical feedback after MRP to radiologists other than upon their own request was infrequent (HDs, 32 – 45 %, PPs, 18 – 32 %).Conclusion: MRP was a widely available, small-volume examination among radiologists in Germany in 2011. The technology mainstay was a 1.5 T surface coil examination including at least one functional MR modality. Dedicated reporting and feedback mechanisms for quality control were underdeveloped.Key Points:• MRI of the prostate was available in at least 67 of 95 German postal regions (71%) in 2011.• MRI of the prostate was most often performed at 1.5T without an endorectal coil in Germany in 2011.• At least two thirds of MRI-examinations of the prostate included both T2WI and at least one functional MR test (mostly DWI, less frequently MRS or DCE) in Germany in 2011.• Structured reporting including graphic elements was offered by less than 20% of participating radiological institutions.• Feedback to radiologists from referring physicians on subsequent test results in patients with MRI of the prostate most frequently came only upon special request by the radiologist.Citation Format:• Mueller-Lisse UG, Lewerich B, Mueller-Lisse UL et al. MRI of the Prostate in Germany: Online Survey among Radiologists. Fortschr Röntgenstr 2015; 187: 703 – 711
Keywords: prostate; MR imaging; MR functional imaging; QA/QC; socioeconomic issues